Aqueous Thunbergia laurifolia leaf extract alleviates paraquat-induced lung injury in rats by inhibiting oxidative stress and inflammation - Sarawoot Palipoch; Chuchard Punsawad; Phanit Koomhin; Prasit Na-Ek; Wasinee Poonsawat; Rungruedi Kimseng; Potiga Chotipong; Kingkan Bunluepuech; Gorawit Yusakul; Prasit Suwannalert (BMC, 2022)
Abstract Background Paraquat (PQ) has been reported to have a high mortality rate. The major target organ of PQ poisoning is the lungs. The pathogenesis of PQ-induced lung injury involves oxidative stress and inflammation. Unfortunately, there is still no effective antidote for PQ poisoning. We hypothesized that aqueous Thunbergia laurifolia (TL) leaf extract is a possible antidote for PQ-induced lung injury. Methods The total phenolic content and caffeic acid content of an aqueous extract of TL leaves were analyzed. Male Wistar rats were randomly divided into four groups (n = 4 per group): the control group (administered normal saline), the PQ group (administered 18 mg/kg body weight (BW) PQ dichloride subcutaneously), the PQ + TL-low-dose (LD) group (administered PQ dichloride subcutaneously and 100 mg/kg BW aqueous TL leaf extract by oral gavage) and the PQ + TL-high-dose (HD) group (administered PQ dichloride subcutaneously and 200 mg/kg BW aqueous TL leaf extract by oral gavage). Malondialdehyde (MDA) levels and lung histopathology were analyzed. In addition, the mRNA expression of NADPH oxidase (NOX), interleukin 1 beta (IL-1β), and tumor necrosis factor alpha (TNF-α) was assessed using reverse transcription-polymerase chain reaction (RT-PCR), and the protein expression of IL-1β and TNF-α was analyzed using immunohistochemistry. Results The total phenolic content of the extract was 20.1 ± 0.39 μg gallic acid equivalents (Eq)/mg extract, and the caffeic acid content was 0.31 ± 0.01 μg/mg. The PQ group showed significantly higher MDA levels and NOX, IL-1β and TNF-α mRNA expression than the control group. Significant pathological changes, including alveolar edema, diffuse alveolar collapse, hemorrhage, leukocyte infiltration, alveolar septal thickening and vascular congestion, were observed in the PQ group compared with the control group. However, the aqueous TL leaf extract significantly attenuated the PQ-induced increases in MDA levels and NOX, IL-1β and TNF-α expressions. Moreover, the aqueous TL leaf extract ameliorated PQ-induced lung pathology. Conclusion This study indicates that aqueous TL leaf extract can ameliorate PQ-induced lung pathology by modulating oxidative stress through inhibition of NOX and by regulating inflammation through inhibition of IL-1β and TNF-α expressions. We suggest that aqueous TL leaf extract can be used as an antidote for PQ-induced lung injury.